OVERTURE “SHÉHÉRAZADE” BY MAURICE RAVEL: GENRE AND SEMANTIC PROJECTIONS - Valeriya ZHARKOVA; Oleksandr ZHARKOV; Ganna RIZAIEVA (Studia Universitatis Babeş-Bolyai. Musica, 2025)
The article is devoted to the study of the genre specificity of M. Ravel’s overture de féerie “Shéhérazade” (1898) and the identification of its important semantic aspects. The non-traditional genre definition of the composition as an overture de féerie reveals the composer’s desire to actualize the theatrical context known to the listener (the féerie genre). The composer seems to extend the “exotic” semantic layer, given in the title by the name of the heroine of the Arabian tales “One Thousand and One Nights”, to the “stereophonic” space of the féerie, and the orchestra completely takes over all the functions of creating the physical and metaphysical dimensions of the féerie. The multidimensionality of the national theatrical genre of the féerie is “folded” in the “Shéhérazade” overture into an orchestral space that contains multilevel projections of the unfolding of extra-musical meanings. This is how the connections between the first orchestral composition and the compositions of the following years - “Waltz” (“choreographic poem”) and “Bolero” (“ballet for orchestra”) – are revealed. The unity of plastic and sound gestures, sensual and deeply hidden from thoughts fantasies will remain a distinctive characteristic of Maurice Ravel’s thinking until his last compositions.